Reforma al Art. 544 del coip, para que la institución jurídica de la caución se aplique en delitos de hasta 10 años, a efecto de garantizar la defensa en libertad, evitando así el hacinamiento carcelario - Peñafiel Jiménez, Josselyn Andrea (2023)
Please, dear reader, please take a closer look at this Degree Project, which is being carried out in the legal field of adjective Criminal Law, entitled “Reform to Art. 544 of the coip, so that the legal institution of bail is applied in crimes of up to 10 years, in order to guarantee the defense in freedom, thus avoiding prison overcrowding”. This degree work is developed based on a set of objectives, which have been verified by means of the vast knowledge of professionals of Criminal Law, covering first of all theoretical concepts such as: The criminal process, precautionary measures, legal institution of the caution, guarantees of the processed person, prison overcrowding, we have also compared our legislation with the legislations of some Latin American countries, likewise several criminal processes have been considered to analyze them and deepen knowledge regarding their inadmissibility, the procedure to follow, the ways in which caution can be granted, its execution and cancellation and the actions of prosecutors and judges against the fixing of the legal figure of caution, the same that is typified in the Organic Integral Penal Code. The application of the legal institution of bail is extremely important, because in this way we guarantee fundamental rights to the defendants as the defense in freedom, until there is an enforceable sentence either ratifying innocence or conviction; This is given after the prosecutors in the hearing of formulation of charges request preventive detention to the judges and these order it, being the caution a mechanism that guarantees the presence of the processed to the following procedural stages and suspends the effects of the preventive detention, until there is an executed sentence, either ratifying the innocence or conviction; the processed person will be able to give caution with his assets or those of a guarantor. Thus, this research work has focused specifically on analyzing each of the concepts that are closely linked to criminal law, the setting of bail, the defense at liberty and the problem of prison overcrowding that concerns us in our country. Finally, the study carried out through the technique of surveys, interviews, and reform proposal, shows that it is feasible, necessary and sufficient to reform Article 544 so that the legal institution of bail is applied in crimes of up to ten years in order to guarantee the defense at liberty, thus avoiding prison overcrowding, corroborating that the mechanisms that suspend the effects of pretrial detention are viable and would not affect the punitive system in any way to apply them in crimes with higher penalties and severity as long as they are admitted by the positivized norm. The accused person may post bail with his or her own assets or those of a guarantor.